The Role of Participatory Ergonomics (PE) in Improving Work Systems in An Effort to Reduce Msds (A Case Study in The Light Steel Industry and Other Manufacturing Industries) - Sukapto, Paulus; Sukamto, Jonathan F.; Darren K, Nathaniel; Tjipto, William J.; Permana , Handy (Greenation International Journal of Engineering Science, 2024)
PE programs have been used as the most effective way to reduce or redesign manual tasks to reduce the incidence of work-related musculoskeletal disorders. This review assesses the evidentiary basis for the claim, explains the various approaches that have been taken using PE methods for several industries, and compiles the learnings obtained from implementing these programs to obtain a safe and comfortable working situation for workers.